Analisis Berita Acara Pemeriksaan (BAP) No: SP-SIDIK/1431/IX/2023/Reskrim tentang Pembunuhan Berdasarkan Keterangan Ahli Pidum (Pidana Umum) - Samara, Finsensius; Saputra, Carolus Hami; Benggu, Christianto Anis; Butarbutar, Raja Rinaldo Sahala; Le, Maria Ratu Mistika Caril Mogi; Mauta, Pretty Angel Bayang; Nggiring, Eufransio Jefferey (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The crime of murder, as stipulated in Article 338 of the Criminal Code, requires a thorough understanding of the law, particularly regarding the fulfillment of the elements of the crime and the criminal responsibility of the perpetrators. This study aims to analyze the opinions of criminal law experts in the investigation of an alleged murder case involving more than one perpetrator, as stated in the expert's Investigation Report (BAP) at the Kupang City Police. The method used is a normative juridical approach, examining statutory provisions, criminal law doctrine, and expert testimony as evidence in the law enforcement process. The results of the study indicate that the application of Article 338 of the Criminal Code must be based on proof of an act that intentionally took the life of another person, whether committed individually or collectively, as stipulated in Article 55 of the Criminal Code. Expert opinion plays a crucial role in helping investigators and law enforcement officers understand the legal construction of a criminal incident objectively and proportionally. Thus, the presence of expert testimony not only strengthens the evidentiary process but also ensures that the application of criminal law is carried out fairly, carefully, and in accordance with the principle of legal certainty.